A Survey of Research on Education in Vietnam through Japanese Bibliographic Sources from 2000 to 2017 - Van, Dao Thu (VNU Journal of Science: Education Research; Vol 34 No 1DO - 10.25073/2588-1159/vnuer.4103, 2018)
In the 20 th and the beginning of 21 st centuries, research of education in Vietnam was popular among Japanese scholars. Their works investigated the whole national education system as well as every detail at each level in that system, appeared in a large number of Japanese translations of law, policies, etc. about education in Vietnam.  Through two major sources, the website http://ci.nii.ac.jp/ where people can search for books and journal articles published in Japan, and contents of the journal Shigaku Zasshi (史學雜誌(Shigaku=Zasshi; Journal of the Historical Society of Japan), number 2, 6, 10 published from 2000 to now (2017), this work aims to summarize and evaluate achievement of Japanese scholars on research about education in Vietnam during that period. This will broaden our view about Vietnamese education in the modern era. This survey is organized into two parts: Part 1: Investigation of research on education in Vietnam from 2000 to now (2017) Part 2: Evaluation of research achievement and its contribution to the development of Vietnam education in the modern era.